A new creep model for SnAgCu lead-free composite solders : incorporating back stress - Nai, S. M. L. (2010)
The paper presents improved constitutive models for SnAgCu solder. In the present study, the constitutive behavior for creep performance of 95.8Sn-3.5Ag-0.7Cu lead-free solder was investigated. The secondary creep stage was focused on. It is shown that the stress exponent n can be well-defined into two stress regimes: low stress and high stress. A new constitutive model, which considered back stress, is proposed to describe the creep behavior of SnAgCu solder. In this model, back stress, being a function of applied shear stress in the low stress regime and particle size, volume fraction, coarsening of IMC particles in high stress regime, is introduced to construct the relationship between the creep strain rate and shear stress. The creep mechanism in these two stress regimes was studied in detail. In low stress regime, dislocations pass through the matrix by climbing over IMC particles. While in high stress one, dislocations are glide-controlled. According to the different creep mechanisms in both stress regimes, the back stress was calculated respectively and then incorporated into Arrhenius power-law creep model. It is demonstrated that the predicted strain rate-shear stress behavior employing the modified creep constitutive model considering back stress is consistent well with the experimental results.